2022
DOI: 10.29141/2218-5003-2022-13-5-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ESG and personal environmental concern on performance of Russian companies

Abstract: The article aims to empirically test the hypothesis on the impact of environmental, social and corporate governance (ESG) practices and employees’ personal environmental concerns on the performance of Russian companies. The methodological basis is the theory of corporate social and environmental responsibility embodied in the ESG concept. Exploratory factor analysis and linear regression are used to assess individual factors of corporate responsibility and personal environmental concerns on the ability of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The design of the survey instrument was improved by an extensive review of the literature, which served as the foundation for developing variables that encapsulate the key dimensions of interest. These variables were subsequently subjected to exploratory factor analysis, a process conducted in the early stages of the study, which confirmed their significance [10]. Therefore, this study aims to scrutinize the complex interplay between latent theoretical constructs, highlighting the causal relationships that cover effects flowing from ESG practices and their end results.…”
Section: Methods and Datamentioning
confidence: 88%
See 1 more Smart Citation
“…The design of the survey instrument was improved by an extensive review of the literature, which served as the foundation for developing variables that encapsulate the key dimensions of interest. These variables were subsequently subjected to exploratory factor analysis, a process conducted in the early stages of the study, which confirmed their significance [10]. Therefore, this study aims to scrutinize the complex interplay between latent theoretical constructs, highlighting the causal relationships that cover effects flowing from ESG practices and their end results.…”
Section: Methods and Datamentioning
confidence: 88%
“…Equally significant is the effort to mitigate the stress arising from the digital transformation of enterprises and its repercussions for the structure of the labour market [9]. Given these exigent circumstances, the attention of researchers is steadfastly fixed upon the realm of human capital and the processes underpinning its accumulation, all in the pursuit of ensuring sustainable development [10,11]. Human capital, in this context, is the stock of knowledge, skills, and capabilities of employees within enterprises.…”
Section: Introductionmentioning
confidence: 99%